PERSELISIHAN PEMUTUSAN HUBUNGAN KERJA DALAM HUBUNGAN INDUSTRIAL DI KOTA TANGERANG - Yusmedi Yusuf; Annie Myranika (SUPREMASI HUKUM, 2021)
Employment developments in Indonesia, influenced by the Industrial Relations between Government and Employers. Industrial relations are needed in the protection of workers in each company. Employment law in legislation, contracts, and cooperative agreements are continuing to experience the dynamics change in industrial relations. Employment issues in Indonesia often arise in industrial relations disputes in particular the case of termination of employment (FLE) unilaterally by the company. Industrial disputes due to layoffs, require the law enforcement aspect through the regulation of Law No.13 of 2003 on Manpower, and Law No.2 of 2004 on Industrial Relations Dispute Settlement. In its implementation, these laws and regulations have not reached the disputing parties, so that problem solving often results in disputes between workers and employers, and the government. This research method use a normative juridical. Primary data and csecondary data were analyzed qualitatively. The bipartite layoff settlement between the company and the workers, in its implementation, has met with many failures in the bargaining process. Department of Labor has attempted to implement Law No.13 of 2003 and Law No.2 of 2004 on Mayor Regulation No.64 of 2016 as an implementation of the mediation settlement. However, the data in the field shows the implementation has not been effective, because industrial dispute settlement case takes approximately 6 months (180 days), exceeds the provisions in Law No.2 of 2004.Keywords: Labor; Industrial Relation; Dispute